THE DARK SIDE OF ACCOUNTING: MATERIALIASME VS SPIRITUALISME DALAM AUDIT - Laksetiowati, Aprilina (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
The auditing profession in Indonesia is currently facing a serious ethical and legitimacy crisis, as reflected in various financial scandals and the weak oversight of public entities. This study aims to explore how auditors in Indonesia negotiate their professional identities amid the pressures of materialistic values and the spiritual-idealist ideals of the profession. Using a critical qualitative approach with a narrative-interpretive method, the research analyzes auditors’ narratives concerning materialistic pressures, ethical dilemmas, and the role of spirituality. Data were collected through in-depth interviews with eight auditors from various audit firms who have experience dealing with ethical challenges. The findings reveal that fee pressures, efficiency targets, and pragmatic business relationships have normalized ethical compromises in audit practices. Auditors construct narratives of justification or resistance to these dilemmas depending on their value backgrounds, job positions, and the presence of ethical communities in their workplaces. Spirituality—derived from both religious beliefs and local wisdom such as Tri Hita Karana—has proven to be a moral force that encourages auditors to uphold professional integrity. However, these spiritual values are often marginalized in a secular, profit-oriented work culture. This study concludes that the ethical crisis in the auditing profession is not merely an individual issue but part of a systemic structure that entraps auditors in value conflicts. The findings contribute to the body of non-Western critical accounting literature and offer implications for audit firms, regulators, and educational institutions to strengthen the ethical and spiritual dimensions in the development of the auditing profession in Indonesia.